Psychologica lreadiness for management as a basis for potential competitiveness in prospective managers - Mitina O.V; Nizovskikh N. A.; Sharafutdinova M. N. (Moscow State University of Psychology and Education, 2017)
The paper presents outcomes of a research on psychological readiness for management in students (future managers). Psychological readiness for management is understood as one's general predisposition towards administrating himself/herself and other people that is based on the system of relevant values. The extent of manifestation of the components of psychological readiness is considered as the basis of potential competitiveness in university graduates.Our empirical research involved students majoring in management (n = 98) aged 18-23 years.The study revealed that management values are highly significant for the respondents and that there are gender differences in value hierarchies.The components of psychological readiness for management were found to be related with indicators of life satisfaction, time perspective and basic values in the students.The outcomes if this research may be applied in higher education, management and career counselling in schools and universities.